Model Sistem Informasi Kampung (Si Kampung) Untuk Penanggulangan Awal Kebakaran Hutan (Studi Kasus Kabupaten Rokan Hulu-Riau) - Maradona, Hendri; Yasdomi, Kiki; Setiawan, Agung; Rifki, Mi'rajul; Dona, Dona (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Forest fires in the Riau province have occurred every year and continue to this day. Many people are reluctant to report to village officials, because of the long distance between community homes and village offices. The condition of the community in Rokan Hulu Regency, most of the community and village officials have used smartphones as a communication medium. To increase the smartphone use of the community and village officials, it is necessary to make an application Sistem Infomasi Kampung (SI Kampung) as a liaison media, so that the positive impact of making the application SI Kampung includes increasing harmonization between village officials and the community, improving service to the community, increasing community participation, improving lives community democracy and encourage community empowerment.